Sharia Pawn For Millennials: Islamic Modern Financial Solutions - Zainol Fata; Ummiyatul Hasanah; Mahbubah (Journal of Islamic Economics, 2024)
This research focuses on the analysis of the concept of pawning in Islam, known as rahn, with the aim of understanding the underlying sharia principles and their application in society. Through a comprehensive literature review, this study examines the definition of rahn from various perspectives of scholars, its legal basis in the Qur'an, hadith, and ijma', as well as the principles and conditions of the validity of the rahn contract. The research method used is literature research with a descriptive-analytical approach, which allows for an in-depth depiction of the rahn phenomenon and analysis based on sharia principles. The results of the study show that rahn is a legal and relevant sharia financial mechanism, with variations in legal interpretation between schools that reflect flexibility in the application of sharia. This study also outlines the limitations in the taking of pawn benefits by murtahin, which must be done with a rahin permit  and in accordance with sharia principles. The implications of this research are the need to increase socialization and education about rahn to the public, standardization  of clear and transparent rahn contracts, and the development of effective dispute resolution mechanisms. This research contributes to a better understanding of rahn as a fair and sustainable sharia financial solution.